Female Gender and Acne Disease Are Jointly and Independently Associated with the Risk of Major Depression and Suicide: A National Population-Based Study. (11th February 2014) - Yang, Yi-Chien; Tu, Hung-Pin; Hong, Chien-Hui; Chang, Wei-Chao; Fu, Hung-Chun; Ho, Ji-Chen; Chang, Wei-Pin; Chuang, Hung-Yi; Lee, Chih-Hung
Abstract : Acne is a common disease in adolescence with female preponderance. It could cause poor self-esteem and social phobia. Previous studies based on questionnaires from several thousands of adolescents showed that acne is associated with major depression and suicide. However, the gender- and age-specific risk of depression and suicide in patients with acne remain largely unknown. Using a database from the National Health Insurance, which included 98% of the population of Taiwan in 2006, we identified patients of acne, major depression, and suicide based on ICD-9-CM codes. Totally 47111 patients with acne were identified (16568 males and 30543 females) from 1 million subjects. The youths of 7–12 years had the highest prevalence of acne (14.39%). Major depression was more common in those with acne (0.77%) than controls (0.56%, P < 0.0001) regardless of gender. Multiple logistic regression showed an increased risk of major depression in women without acne (OR = 1.85, 95% CI 1.75–1.96). The risk is additive in women with acne (OR = 2.78, 95% CI 2.43–3.17). Similar additive risk of suicide was noticed in women with acne. In conclusion, acne and gender, independently and jointly, are associated with major depression and suicide. Special medical support should be warranted in females with acne for the risk of major depression and suicide.